Quick & easy low-fat recipes : lose weight-feel great - Graimes, Nicola (Watkins Publishing, 2010)
The World Health Organisation recommends that overall fat intake should make up no more than 20-30 per cent of our daily calories. This book features recipes that come with an easy-to-follow nutritional breakdown, detailing overall fat content, saturated fat level and calories, as well as symbols highlighting nutritional benefits